[PP.17.02] THE EFFECT OF INTENSIVE LIPID LOWERING VERSUS USAUL LIPID LOWERING ON RENAL FUNCTION IN PATIENTS WITH ATHEROSCLEROTIC RENAL ARTERY STENOSIS UNDERGOING RENAL ARTERY STENTING. (September 2017) - Jiang, X.; Peng, M.; Dong, H.; Li, B.; Zou, Y.; Wu, H.
Abstract : Objective: To investigate how intensive lipid lowering affects renal function when compared with standard lipid lowering in patients with atherosclerotic renal artery stenosis undergoing renal artery stenting. Design and method: Between June 2013 and December 2014, a total of 150 patients with atherosclerotic renal artery stenosis undergoing renal artery stenting were randomly (1:1) assigned to receive intensive lipid lowering [the goal of low density lipoprotein cholesterol, LDL- C<1.8 mmol/L] or usaul lipid lowering (the goal of LDL -C 1.8∼3.3 mmol/L). All patients received rosuvastatin. LDL-C was adjusted to the goal within two months and appropriate treatment was maintained. No significant difference existed in the treatment regimens other than lipid-lowering therapy between the two groups. The primary end points were estimated glomerular filtration rate (eGFR) and urinary albumin to creatinine ratio at 6 months. The secondary end points were the number of antihypertensive medications, the clinic blood pressure, the restenosis rate, cardiovascular clinical events at 6 months. Results: The baseline clinical characteristics were comparable between two groups. At 6 month follow-up, LDL-C was lower in the patients with intensive lipid lowering than with usual lipid lowering[(1.51 +/− 0.32) vs (2.32 +/− 0.47) mmol/L, P < 0.01]; eGFR [(92.0 +/− 29.3) versus (79.5 +/− 19.4) mL/(min/1.73 m 2 ), P < 0.01] and the increase of eGFR [16.7(3.6–24.6) vs 1.5(−9.5–8.7) mL/(min/1.73 m 2 ), P < 0.01] were higher in the patients with intensive lipid lowering than with usaul lipid lowering;urinary albumin-creatinine ratio[45.3(19.8–64.0) vs 55.4 (26.0–121.8) mg/g, P = 0.037] was lower and the decrease of urinary albumin-creatinine ratio was higher[31.7(2.3–54.4) vs −6.6 (−17.6–31.1) mg/g, P < 0.01] in the patients with intensive lipid lowering than with usaul lipid lowering. In term of secondary end points, the number of antihypertensive medications and the clinic blood pressure decreased in both the two groups. But there was no significant difference between the two groups. The restenosis rate and major clinical events were similar between two groups. Conclusions: In patients with atherosclerotic renal artery stenosis undergoing renal artery stenting, renal function is improved greater in the intensive lipid lowering group than in the usaul lipid lowering group.